Experience of Acute Respiratory Infections Treatment in Children with Combination Drug Askoril - S.A. Kramarev; V.V. Yevtushenko; A.I. Markov (Zaslavsky O.Yu., 2015)
Respiratory diseases are mostly accompanied by changes of mucociliary clearance. The paper presents the possibility of using combination preparation with different points of application for the treatment of tracheobronchial drainage disturbances in respiratory diseases in children.